State versus market : have Asian currency crises affected the reform debate? - Stiglitz, Joseph E. (Published for Bangladesh Economic Association [by] University Press, 1999)
Transcript of a lecture organized by Bangladesh Economic Association in Dhaka on March 14, 1999.